SYNTHESIS, CHARACTERIZATION AND ANTI-MICROBIAL ACTIVITIES OF NOVEL THIAZOLE DERIVATIVES - G. SARAVANAN,; V. ALAGARSAMY,; T.G.V. PAVITRA,; G. CHANUKYA KUMAR,; Y. SAVITHRI,; L. NARESH,; P. AVINASH, (International Journal of Pharma and Bio Sciences, 2010)
In the present study, a novel thiazoles were synthesized by incorporation of pyrazole moiety at 2nd position of 2-hydrazinyl-N-(4-phenylthiazol-2-yl) acetamide (5) by treating with chalcones (7a-7j). The chemical structures of the synthesized compounds were confirmed by means of IR, 1H-NMR, Mass spectral and Elemental analysis. These compounds were screened for anti-bacterial (Staphylococcus aureus ATCC 9144, Staphylococcus epidermidis ATCC 155, Micrococcus luteus ATCC 4698, Bacillus cereus ATCC 11778, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 2853, and Klebsiella pneumoniae ATCC 11298)) and anti-fungal (Aspergillus niger ATCC 9029 and Aspergillus fumigatus ATCC 46645) activities by paper disc diffusion technique. Most of the synthesized compounds exhibited significant anti-bacterial and anti-fungal activities. Among the synthesized compounds, 2-(5-(4-hydroxyphenyl)-3-phenyl-4,5-dihydropyrazol-1-yl)-N-(4phenylthiazol-2-yl)acetamide (8f) was found to exhibit the highest anti-bacterial activity and 2-(5-(4hydroxy-3-methoxyphenyl)-3-phenyl-4,5-dihydropyrazol-1-yl)-N-(4-phenylthiazol-2-yl)acetamide(8j) exhibited highest anti-fungal activity.